Extreme hypofractionation for early prostate cancer: Biology meets technology. (November 2016) - De Bari, Berardino; Arcangeli, Stefano; Ciardo, Delia; Mazzola, Rosario; Alongi, Filippo; Russi, Elvio G.; Santoni, Riccardo; Magrini, Stefano M.; Jereczek-Fossa, Barbara A.; ,
Highlights: An exhaustive review of extreme hypofractionated prostate radiotherapy is presented. Available clinical data encourage hypofractionation in prostate cancer treatment. Several technological improvements address the issue of accuracy in hypofractionation. We present outcome results from 20 clinical studies enrolling more than 40 patients. Abstract: The aim of this review is to present the available radiobiological, technical and clinical data about extreme hypofractionation in primary prostate cancer radiotherapy. The interest in this technique is based on the favourable radiobiological characteristics of prostate cancer and supported by advantageous logistic aspects deriving from short overall treatment time. The clinical validity of short-term treatment schedule is proven by a body of non-randomised studies, using both isocentric (LINAC-based) or non-isocentric (CyberKnife ® -based) stereotactic body irradiation techniques. Twenty clinical studies, each enrolling more than 40 patients for a total of 1874 treated patients, were revised in terms of technological setting, toxicity, outcome and quality of life assessment. The implemented strategies for the tracking of the prostate and the sparing of the rectal wall have been investigated with particular attention. The urinary toxicity after prostate stereotactic body irradiation seems slightly more pronounced as compared to rectal adverse events, and this is more evident for late occurring events, but no worse as respect to conventional fractionation schemes. As far as the rate of severe acute toxicity is concerned, in all the available studies the treatment was globally well tolerated. While awaiting long-term data on efficacy and toxicity, the analysed studies suggest that the outcome profile of this approach, alongside the patient convenience and reduced costs, is promising. Forty-eight ongoing clinical trials are also presented as a preview of the expectation from the near future.